ChemInform Abstract: L‐Proline Nitrate: A Recyclable and Green Catalyst for the Synthesis of Highly Functionalized Piperidines. Issue 40 (October 2015) - Agrawal, Nikita R.; Bahekar, Sandeep P.; Sarode, Prashant B.; Zade, Sanjio S.; Chandak, Hemant S.
Abstract The application of the ionic liquid L‐proline nitrate as catalyst for the pseudo‐five component reaction of aromatic aldehydes, anilines, and β‐dicarbonyl compounds is demonstrated.